Metabolic profiling on the analysis of different parts of Schisandra chinensis based on UPLC-QTOF-MS with comparative bioactivity assays - Liu, Jiushi; Mu, Xinlu; Liang, Jinmei; Zhang, Jianuo; Qiang, Tingyan; Li, Hongbo; Li, Bin; Liu, Haitao; Zhang, Bengang (Frontiers in Plant Science, 2022)
The Schisandra chinensis (S. chinensis) is an important edible plant, previous phytochemical research has focused on the S. chinensis fruit (SF) due to its long history as a traditional Chinese medicine. S. chinensis fruit was used as an astringent tonic to astringe the lungs and kidneys, replenish energy, promote the production of body fluids, tonify the kidney, and induce sedation. The components of S. chinensis, such as its stems (SS), leaves (SL), and roots (SR), have drawn little attention regarding their metabolites and bioactivities. In this study, a strategy of combining a chemical database with the Progenesis QI informatics platform was applied to characterize the metabolites. A total of 332 compounds were tentatively identified, including lignans, triterpenoids, flavonoids, tannins, and other compound classes. Heatmap and principal component analysis showed remarkable differences in different plant parts. By multiple orthogonal partial least-squares discriminant analyses, 76 compounds were identified as potential marker compounds that differentiate these different plant parts. Based on the variable influence on the projection score from OPLS-DA, the active substances gomisin D, schisandrol B, schisantherin C, kadsuranin, and kadlongilactone F supported that the biological activity of the roots was higher than that of the fruit. The substances can be used as marker compounds in the plant roots, which likely contribute to their antioxidant and anti-inflammatory activities. The plant roots could be a new medicinal source that exhibits better activity than that of traditional medicinal parts, so the roots are worth exploring.